Análise das configurações da Regional CIC: um estudo de caso do comportamento emergente - Bazan, Luciana Borges (2012)
Understanding the emergent behavior in urban areas is essential to study more efficiently and drive public policy. Whereas the urban emergencies are elements present in the daily life of cities is not possible for the state not take them into account when formulating their actions pubic area. Taking as its premise that society is a living body, where each agency fulfills a function, we seek to equip the way for appropriate policy actions to urban emergencies. The objective of this study is to reflect on the emergent behavior from the case study of the Regional CIC, taking into account aspects of planning policy and those related to self-organization of spaces and territories. The study, in its methods of research is exploratory and descriptive, analytical and design configured as a case study. The analysis is qualitative, seeking the relationship of the case described in the literature studied and the universe of research is the city of Curitiba, with the direct sampling the Regional CIC. Through the literary study arose that the emergent behavior in urban areas is a constant, especially in cities or territories in constant development as is the case of Curitiba - PR. The emerging systems are the result of processes that involve order and disorder and self-organization, and network systems as an element in its constitution. The urban emergencies, following the emergentist concepts, can not be predicted or planned, arise from a self-organizing process, from the bottom up, which produce lower levels of new properties with complex traits. By analyzing the creation of the Regional CIC realizes that many emerging elements are present, and highlighted the following: Creation of the Industrial City of Curitiba, regionalization and territorialization, deterritorialization (dismemberment of the neighborhood), sectoral networks planned or unplanned, and interorganizational and emphasis to human and ethical aspects. It is felt that public policies have analyzed emerging elements because they are descentralizas, working in the system of networks, exchange information in the community and seek to influence, not control, the territories in development. It can be concluded that public policy should not seek control of urban movements and emerging processes, but encourage creativity and self-organization of social groups, being herself, one of the components of urban systems emerging.